Clonally-Related Composite Classic Hodgkin Lymphoma and Follicular Lymphoma. (28th October 2021) - Larson, D P; Ketterling, R P; He, R; Shi, M; McPhail, E D; Yuan, J
Abstract: Introduction/Objective: Composite classic Hodgkin lymphoma and follicular lymphoma (CHLFL), defined as CHL and FL occurring simultaneously at the same site, is rare and poorly understood. While both Hodgkin/Reed-Sternberg (HRS) cells and FL are thought to be derived from germinal center B-cells, the relationship between CHL and FL when coexistent is unclear. Here, we present two cases of CHLFL and show that the CHL and FL components have a clonal relationship by FISH. Methods/Case Report: Case #1 is a 50-year-old man with abdominal and mediastinal lymphadenopathy. An excised mesenteric lymph node showed two distinct components diagnostic for FL, grade 1-2 and CHL. Case #2 is a 63-year- old woman with a history of FL with transformation to diffuse large B-cell lymphoma. Cytogenetic studies showed a complex karyotype with an add(9p), del(10q), and trisomy 16. Post-treatment imaging revealed left axillary adenopathy. An excised axillary lymph node showed CHL with peripheral areas of FL, grade 3A. Both cases had areas of typical FL with BCL2-positive phenotype and no significant CD30/CD15 expression. HRS cells were CD45/CD20-negative, expressed CD30 (strong), CD15, and PAX5, and were present in a mixed inflammatory background. No EBV RNA was present by in situ hybridization. Interestingly, HRS cells in case #1 expressed both BCL6 and BCL2. FISH was performed in both cases. Case #1 had a BCL2 rearrangement in 48% of FL nuclei and in 100% of HRS cells. In case #2, targeted probes were used based on prior cytogenetic results. Here, 47% of FL nuclei and 44% of HRS cells had a 16p duplication; additionally, 32% of HRS cells had an unbalanced IGH rearrangement with loss of the IGH variable region, suggesting possible clonal evolution. No rearrangement of BCL2 or BCL6 was present. An additional 27 CHLFL cases from the literature were reviewed. CHLFL was mostly nodal and occurred in late adulthood in patients with or without a history of FL. It presented at advanced clinical stage, with a 5-year overall survival of 22%. BCL2 expression in HRS cells was common. Bone marrow involvement was 45% (5/11) and consisted of FL exclusively. Five of six tested cases demonstrated BCL2/IGH rearrangement in both FL and HRS cells. Results (if a Case Study enter NA): NA Conclusion: Composite CHL and FL are often clonally related and may share a common progenitor B-cell origin – likely a germinal center B-cell – from which additional genetic abnormalities are acquired to develop two distinct lymphomas.